+0  
 
0
93
1
avatar

Consider the following pair of equations:

y = 3x + 3
y = x − 1

Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form.

 Mar 12, 2021
edited by Guest  Mar 12, 2021
 #1
avatar+118069 
+1

Look  at the second equation

 

y  = x  -1

 

y + 1  =   x                sub this into  the first equation for  x

 

y = 3 ( y + 1)  + 3

 

y = 3y + 3 + 3

 

y  = 3y  + 6

 

y  -3y  =  6

 

-2y   =  6

 

y =   6 / -2     =   -3

 

And   x  =  y + 1    =   -3  + 1   =  -2

 

(x , y)  = (-2, - 3)

 

 

cool cool cool

 Mar 12, 2021

22 Online Users

avatar
avatar
avatar